Dependability Analysis of Weather Monitoring Systems Considering Different Redundancy Mechanisms - Lima, Vinícius Gabriel Pereira; Andrade, Ermeson; Araújo, Danilo R. B. de (Anais do Simpósio em Sistemas Computacionais de Alto Desempenho (SSCAD), 2025)
The increasing occurrence of extreme weather events makes precipitation forecasting essential for disaster mitigation. The Internet of Things (IoT) has enhanced weather monitoring, but ensuring system availability and reliability remains a challenge. This study evaluates the impact of redundancy on system dependability, focusing on availability and reliability. Models were developed to compare a system without redundancy to one incorporating redundancy in critical components. Using Stochastic Petri Nets (SPNs), we analyzed their behavior under different failure and repair scenarios. Results show that redundancy significantly improves availability, reduces the probability of failures, and minimizes downtime, reinforcing its importance in the resilience of climate monitoring systems.